Improvement of the ecological safety of road transport in the use of alternative fuel and exhaust converters - Shmandiy, Volodymyr; Kharlamova, Olena; Rigas, Tetyana (Lviv Politechnic Publishing House, 2017)
The aim of the research was to reduce ecological danger caused by vehicles through the use of combined fuel and improved designs converters of exhaust gases. The use of obsolete structures of a catalytic analyzer on cars and the provision of periodic purging of catalytic units can significantly reduce soot emissions without making changes to the design of the engine. It was established that the use of a mixture of diesel fuel with biofuels (made involving waste) reduces the toxicity of exhaust gases by 30–35 % and saves hydrocarbons.
Keywords: ecological danger; road transport; exhaust; converter; biofuels; ecological safety; carbon black